34. BRAF V600E MUTATION DETECTION IN CELL BLOCKS OF THYROID FINE NEEDLE ASPIRATION CYTOLOGY SAMPLES. (February 2015) - Leslie, Connull; Grieu-Iacopetta, Fabienne; Frost, Felicity; Kumarasinghe, M. P.
Abstract : Introduction: BRAF mutation c.1799T>A, p.Val600Glu (or V600E) in thyroid neoplasms is exclusively associated with papillary carcinoma (PTC) or anaplastic thyroid carcinoma. Demonstration of BRAF mutation has been suggested as a supplement to confirmation of PTC in cytology material. Recently a V600E mutation specific antibody has been developed. We aim to assess the feasibility of testing for BRAF V600E mutational status in cytology (cell block) material. Methods: 39 adequate cell blocks (CBs) and 18 available follow-up histology cases were tested by immunohistochemistry (IHC) (clone VE1, 1:400, Spring Biosciences, Pleasanton, California, using Optiview amplification kit) and molecular methods (castPCR: Competitive Allele Specific Taqman PCR, Life Technologies, CA, USA), followed by single-strand confirmation polymorphism (SSCP) if required. All cell blocks tested included H+E sections to confirm adequacy of abnormal cells. Any fine granular cytoplasmic staining in abnormal cells was considered as a positive IHC result. DNA content on CBs ranged from 2.4–54.1 ng/μL and was considered adequate for both molecular methods. Results: Table shows test results for BRAF mutation in cytology and histology for IHC or molecular methods. Conclusions: BRAF V600E mutation assessment in thyroid cell block cytology material is feasible although the role in diagnostic algorithm requires further investigation. Specificity of CB BRAF positivity by both IHC and molecular methods was 100% (no false positive findings). Discrepancies noted between IHC and molecular methods requires further investigation.